Transformasi Komunikasi Seniman Jalanan: Etnografi Digital Strategi Performa pada Platform TikTok - Mega Mutia Maeskina; Nyimas Sri Rahayu; Rifka Noor Hasanah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of digital technology has created a new form of street performance that is no longer limited to face-to-face interaction but is extended through live streaming on platforms such as TikTok. This phenomenon remains underexplored, particularly regarding the communication strategies used by digital street performers to build interaction with online audiences. This study employs a qualitative approach with a digital ethnography method, using online participatory observation, in-depth interviews, and digital documentation of performers who actively conduct live streaming in public spaces without directly asking for money, but instead rely on digital appreciation. The findings reveal that their communication strategies unfold in five stages: prepare, opening, action, closing, and reputation. These stages illustrate a shift from conventional hard selling to soft selling practices based on self-presentation, entertainment narratives, and emotional engagement. The phenomenon reflects not only technical adaptation but also cultural transformation, where identity, digital capital, and social relations are reshaped by platform logics. This study contributes to the development of digital communication studies through a digital ethnography perspective, while also providing practical implications for street performers in leveraging social media for career sustainability.